Structure-property relationships in bio-based polyurethane/carbon nanotube composite coatings revealed by principal component analysis - Muhammad Abdurrahman, Munir; David, Fernando; Imam Shofid, Alaih; Fitria, Rahmawati; Abdul, Rohman (Elsevier Ltd., 2026)
This study investigates the structural, thermal, morphological, and electrical properties of bio-based polyurethane (PU) composites reinforced with carbon nanotubes (CNTs). PU was synthesized using methylene diphenyl diisocyanate (MDI) and palm kernel oil-derived polyol, while CNTs were incorporated in varying concentrations (1 %, 2 %, 5 %, and 10 %) via a sonication-assisted solution casting method. The chemical structure and successful incorporation of CNTs were confirmed using Fourier Transform Infrared Spectroscopy (FTIR), revealing the preservation of the PU backbone and the presence of non-covalent interactions such as hydrogen bonding. Principal Component Analysis (PCA) of FTIR data demonstrated effective differentiation between PU and PU/CNT composites based on subtle changes in the fingerprint region. Field Emission Scanning Electron Microscopy (FESEM) confirmed a uniform and well-integrated dispersion of CNTs in the PU matrix, with minimal aggregation, supporting effective nanofiller incorporation. Thermal analyses using Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC) revealed that CNTs improved the thermal stability, delayed decomposition onset, and increased residual char content, particularly at 5–10 wt% CNT. These enhancements were attributed to CNTs' barrier effect and high thermal conductivity. Electrochemical Impedance Spectroscopy (EIS) further demonstrated a significant reduction in bulk resistance with increasing CNT concentration, confirming enhanced electrical conductivity and the formation of conductive networks. The PU/CNT composites exhibited characteristic impedance behavior in line with the Randles circuit model, supporting their potential for electrochemical applications. Overall, the results indicate that CNT-reinforced PU composites possess enhanced thermal, structural, and electrochemical properties, making them promising candidates for flexible electronics, electrochemical sensors, and anti-corrosion coatings.